Consensus statement on improving the mental health of high performance athletes - Henriksen, K.; Schinke, R.; Moesch, K.; McCann, S.; Parham, W. D.; Hvid Larsen, C.; Terry, P. (International Journal of Sport and Exercise Psychology, 2020)
This consensus statement is the product of an international Think Tank on the initiative of the International Society of Sport Psychology. The purpose of the Think Tank was to unify major sport psychology organizations in a discussion of the current status and future challenges of applied and research aspects of athlete mental health. The contributors present six propositions and recommendations to inspire sport organizations and researchers. The propositions are: Mental health is a core component of a culture of excellence; Mental health in a sport context should be better defined; Research on mental health in sport should broaden the scope of assessment; Athlete mental health is a major resource for the whole athletic career and life post-athletic career; The environment can nourish or malnourish athlete mental health; and Mental health is everybody`s business but should be overseen by one or a few specified members. It is recommended that researchers unite to develop a more contextualized definition of athlete mental health and more comprehensive strategies of assessment, as well as join forces with sporting organizations to investigate sustainable elite sport environments and the role of the mental health officer. Sport organizations are advised to recognize athlete mental health as a core component of a healthy elite sport system and a key indicator of their effectiveness, support research initiatives, and to promote the mental health literacy of all their staff while engaging a mental health officer with the responsibility to oversee a support system.